Plan de Negocios para el hotel-escuela de la Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López - Basurto Valencia, Erika María (2012)
The study aimed to develop a business plan implemented at the Hotel – Escuela ESPAM MFL to determine the financial viability of the services that will offer the hotel and to manage resources in an appropriate manner. The scope of the investigation was entirely positive, since the results obtained in the market study were satisfactory. The Hotel - Escuela is located at El Limon, within the grounds of the ESPAM MFL. The methodology used was the application of inductive methods - deductive, analytic - synthetic, also applied techniques such as the survey of resident and nonresident visitors with questions related to the hosting service, catering and recreational areas and interview it was applied for information on the current status of the project assisted by field visits and the statistical method for numerical information. The Hotel – Escuela has been created primarily for student practice of engineering degree in tourism ESPAM MFL, the establishment has 34 rooms on 4 singles, 12 doubles, 6 triples, 6 matrimony and 6 suites with a capacity of 70 pax, the restaurant has capacity for 94 pax and 200 pax ballroom. And through the Business Plan could know the profitability of the Hotel – Escuela because it is a fundamental tool, since it is the strategic foundation of any business to succeed.